2018
DOI: 10.1161/strokeaha.118.021579
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Quality of Preinterventional Reperfusion in Patients With Direct Access to Endovascular Treatment

Abstract: Background and Purpose-Preinterventional reperfusion before endovascular treatment (ET) is a benefit of bridging with intravenous tPA (tissue-type plasminogen activator). However, detailed data on reperfusion quality and rates of obviating ET in a cohort of patients with immediate access to ET is lacking. Purpose of this analysis was to evaluate prevalence and quality of preinterventional reperfusion in mothership patients. Methods-All mothership patients (n=627) from a prospective registry subjected to angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 29 publications
3
39
2
Order By: Relevance
“…13,16,19,20 However, this study showed a lower incidence of thrombus resolution, which may be the result of a difference in definition; we defined thrombus resolution as complete recanalization before the intervention. 16,25 While the association of IVT and changes in thrombus location has been demonstrated, 20 especially in patients with preinterventional reperfusion, 25,26 the association was not present in other thrombus migration studies. 13,16 Our study found that in patients treated with IVT, both thrombus migration and resolution were more frequent.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…13,16,19,20 However, this study showed a lower incidence of thrombus resolution, which may be the result of a difference in definition; we defined thrombus resolution as complete recanalization before the intervention. 16,25 While the association of IVT and changes in thrombus location has been demonstrated, 20 especially in patients with preinterventional reperfusion, 25,26 the association was not present in other thrombus migration studies. 13,16 Our study found that in patients treated with IVT, both thrombus migration and resolution were more frequent.…”
Section: Discussionmentioning
confidence: 96%
“…Kaesmacher et al 13 included patients with both direct (angiographic) and indirect evidence of thrombus migration by evaluating perfusion deficits within the lenticulostriate artery territory. 26 In our study, only direct evidence was used. The association between thrombus migration and a lower chance of successful reperfusion was also previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying New Approaches to Optimize Thrombus Characterization for Predicting Early Recanalization and Reperfusion With IV tPA Using Serial CT Angiography (INTERRSeCT) (13) INTERRSeCT is a prospective multi-center hospital-based cohort of patients treated with intravenous alteplase comparing the rates of early recanalization in 684 patients. Patient eligibility included the following: presentation to the emergency department with symptoms consistent with ischemic stroke 12 h from last known well, age at least 40 years, and a baseline CTA (before alteplase bolus, if given) with evidence of a symptomatic intracranial thrombus.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The primary radiological outcome was recanalization, while the primary clinical outcome was functional independence, as measured by the mRS (range, 0 [no symptoms] to 6 [death]) at 90 days. Details about this study have been published elsewhere (13). A subset of 507 patients were included in this study, and the rest of the patients were excluded for being a participant in the PROVE-IT study.…”
Section: Data Sourcesmentioning
confidence: 99%